Value at risk, Equity and Diversification - Udo Broll; Jack E. Wahl (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2006)
The value at risk measure attempts to summarize in a single number market value risk of a portfolio of financial assets.The paper focuses on the interaction between the solvency probability of a bank, on one hand, and the diversification potential of its portfolio, on the other hand, when optimum endowment of equity capital is to be determined. Given the necessity to achieve some confidence level of solvency we demonstrate that diversification pays when optimizing the use of the equity resource.
Keywords: G38; G28; G21; 330; equity capital; banking; value at risk; diversification; risk management; asset-liability management